Biometric Infrastructures and the Indian Public Distribution System - Silvia Masiero (South Asia Multidisciplinary Academic Journal)
This paper reflects on the author’s nine-year research on the transformation of India’s Public Distribution System (PDS) enacted through digital technologies first and, more recently, through Aadhaar’s biometric infrastructure. Based on the experiences of two states, Kerala and Karnataka, which adopted biometric identification in their ration shops, the paper illustrates the effects of the transition to an Aadhaar-based PDS, on both program governance and recipients’ entitlements. It argues that, while designed with the objective of combating the rice mafia resulting in foodgrain diversion, a biometric PDS does not prevent the exclusion errors pervading the program, and supports the transition to a cash transfer system whose developmental outcomes are still uncertain. Contributing to the debate on coded citizenship in South Asia, this paper reflects on the transformative power that biometric infrastructures yield over food security schemes, and considers different ways a computerized PDS may be tailored for the inclusion of vulnerable groups.